2013
DOI: 10.4300/jgme-d-12-00249.1
|View full text |Cite
|
Sign up to set email alerts
|

PEARLs of Wisdom: Impact of a New Block Conference on Pediatrics Resident Attendance, Satisfaction, and Learning

Abstract: Background Resident attendance and participation at didactic conferences is often limited owing to time demands. In 2010, University of Wisconsin-Madison pediatrics residency eliminated all noon conferences and implemented a new block format, PEARL (Pediatric Education and Active Resident Learning). Objective The purpose of this study was to assess whether changes in a conference structure improved resident attendance, distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Evaluation of extended interactive case-based learning shows that, when compared to traditional didactic experiences, it results in signi cantly improved resident attendance, lowered distractibility, and improved resident satisfaction. 12 It would be interesting to compare levels of effectiveness of AHD in studies that use mixed interactive methods, including role plays, simulations, and/or case-based learning, versus studies that depend almost exclusively on didactic presentations.…”
Section: Results In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of extended interactive case-based learning shows that, when compared to traditional didactic experiences, it results in signi cantly improved resident attendance, lowered distractibility, and improved resident satisfaction. 12 It would be interesting to compare levels of effectiveness of AHD in studies that use mixed interactive methods, including role plays, simulations, and/or case-based learning, versus studies that depend almost exclusively on didactic presentations.…”
Section: Results In Contextmentioning
confidence: 99%
“…Resident learning is also chronically interrupted by frequent noti cations and questions from inpatient wards. 11,12 An alternative teaching strategy, the academic half-day (AHD), has grown in popularity because it provides a block of protected learning time that aims to improve trainees' attendance and active engagement without interruption. 10 The assumption is that learning and knowledge acquisition is facilitated by uninterrupted massed practice over frequently disrupted distributed practice.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an AHD can positively impact resident attendance. (Moreno et al, 2013;Zastoupil et al, 2017) Learner perception of educational time has also been shown to improve in the AHD model. (Moreno et al, 2013;Ha et al, 2014;Eid et al, 2015;Robbins, Sullivan and Smith, 2018) Additional studies in graduate medical education have found the AHD may improve medical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…(Moreno et al, 2013;Zastoupil et al, 2017) Learner perception of educational time has also been shown to improve in the AHD model. (Moreno et al, 2013;Ha et al, 2014;Eid et al, 2015;Robbins, Sullivan and Smith, 2018) Additional studies in graduate medical education have found the AHD may improve medical knowledge. (Batalden, Warm and Logio, 2013;Ha et al, 2014) (Eid et al, 2015;Robbins, Sullivan and Smith, 2018) A study by Winter et al is the only AHD study which did not show significant improvement in resident knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation